Теоретические и экспериментальные исследования теплопередачи и кипения в выпарных аппаратах со стекающей пленкой - Данилов, Юрий Борисович; Ульев, Леонид Михайлович (НТУ "ХПИ", 2012)
The mathematical model for that transfer with liquid film evaporation in the circle confuser was created in the paper. It was shown that the created model fit to experimental data. The equations for calculate of liquid film thickness, velocity, temperature, local and average Nusselt number.
Keywords: теплоперенос; теплоотдача; тепловая нагрузка; пограничный слой; выпаривание; греющий пар; теплообмен